Sustainability Analysis of MSMES in Sampang Regency Based on Multidimensional Scaling - Kholid Murtadlo; Deny Utomo (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Micro, Small and Medium Eterprises (MSMES) have a very important role in a country's economic growth, so the desire for MSMES is very necessary in the long term. MSMES have been recognized as an important driving force to alleviate some of the economic challenges faced by a country and can overcome poverty alleviation and reduce poverty rates. The main objective of the Sustainable Livelihood Approach in MSMES is to promote appropriate livelihoods for poverty alleviation. An important aspect of the Sustainable Livelihood Approach scheme is related to the systematic understanding and determination of obstacles arising from aspects of financial, natural, human, physical and social capital. The aim of this research is to analyze MSMES in Sampang Regency on the aspects of financial, natural, human, physical and social capital. This research method uses Rapid Appraisal for Fisheries (RAPFISH). The research results show the highest leverage value for financial capital in indicators for the availability of business permits, natural capital for the affordability of prices for main raw materials, human capital for the level of business knowledge, physical capital for road conditions, and social capital for collaboration with fellow MSMES players. The results of the analysis vary according to three categories of poverty (less sustainable, sufficient sustainable, good sustainable).